RETRACTED: Tlr5 deficiency exacerbates lupus-like disease in the MRL/lpr mouse model - Alajoleen, Razan M.; Oakland, David N.; Estaleen, Rana; Shakeri, Aida; Lu, Ran; Appiah, Michael; Sun, Sha; Neumann, Jonathan; Kawauchi, Shimako; Cecere, Thomas E.; McMillan, Ryan P.; Reilly, Christopher M.; et al. (Frontiers in Immunology, 2024)
Leaky gut has been linked to autoimmune disorders including lupus. We previously reported upregulation of anti-flagellin antibodies in the blood of lupus patients and lupus-prone mice, which led to our hypothesis that a leaky gut drives lupus through bacterial flagellin-mediated activation of tolllike receptor 5 (TLR5). Here, we investigated lupus-like disease in MRL/lpr mice with global Tlr5 deletion. Contrary to our hypothesis that the deletion of Tlr5 would attenuate lupus, our results showed exacerbation of lupus with Tlr5 deficiency in female MRL/lpr mice. Remarkably higher levels of proteinuria were observed in Tlr5 -/-MRL/lpr mice suggesting aggravated glomerulonephritis. Histopathological analysis confirmed this result, and Tlr5 deletion significantly increased the deposition of IgG and complement C3 in the glomeruli. In addition, Tlr5 deficiency significantly increased renal infiltration of Th17 and activated cDC1 cells. Splenomegaly and lymphadenopathy were also aggravated in Tlr5 -/-MRL/lpr mice suggesting impact on lymphoproliferation. In the spleen, significant decreased frequencies of regulatory lymphocytes and increased germinal centers were observed with Tlr5 deletion. Notably, Tlr5 deficiency did not change host metabolism or the existing leaky gut; however, it significantly reshaped the fecal microbiota. Future studies will elucidate the underlying mechanisms by which Tlr5 deficiency modulates host-microbiota interactions to exacerbate lupus.